1997
DOI: 10.1108/02656719710165383
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing a successful transition from ISO 9000 to TQM

Abstract: This paper is the first of two which seek to further the debate about the role and value of ISO 9000 as a route to TQM. In particular, outlines a framework by which the next phase of a longitudinal study of 115 ISO 9000 registered organizations may be conducted. Shows that very little empirical work has been published which explores this transition beyond ISO 9000 to TQM. Moreover, what literature does exist is divided on the issues, for example on whether or not it is beneficial to obtain ISO 9000 before emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 15 publications
1
45
0
6
Order By: Relevance
“…(Askey and Dale, 1994;Bradley, 1994;Stephens, 1994;Meegan and Taylor, 1997;Van der Wiele et al, 1997;Brown et al, 1998;Kanji, 1998;Quazi and Padibjo, 1998;McAdam and McKeown, 1999;Lee, 1995;Jones et al, 1997;Singels et al, 2001;Yahya and Goh, 2001;Williams, 1997;Kochan, 1993;Brecka, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…(Askey and Dale, 1994;Bradley, 1994;Stephens, 1994;Meegan and Taylor, 1997;Van der Wiele et al, 1997;Brown et al, 1998;Kanji, 1998;Quazi and Padibjo, 1998;McAdam and McKeown, 1999;Lee, 1995;Jones et al, 1997;Singels et al, 2001;Yahya and Goh, 2001;Williams, 1997;Kochan, 1993;Brecka, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting question for further investigation is whether the demonstration to other 31 managers that substantial employee involvement developments do not in fact require strategic interventions by HR managers will have lasting negative effects for the development of HRM. It has been suggested that to move from ISO 9000 to TQM requires increased levels of understanding and motivation by employees (Meegan and Taylor, 1997); whether this will provide more of an opening for HR managers to establish themselves remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…Using Vidal's distinction, the levels of involvement demanded by quality initiatives envisaged by criticised it for not dealing adequately with employee involvement, and too focused on production and a limited number of support processes (EU, 13 1997). Total Quality Management (TQM) is by design more radical than ISO 9000, going further in breaking down hierarchies and traditional barriers inside firms, notably through a stronger emphasis on increased teamwork (Meegan and Taylor, 1997). However, this challenges management to innovate radically rather than incrementally and therefore reduces its attractiveness.…”
Section: Quality and Involvement In The Ukrainian Contextmentioning
confidence: 99%
“…Las buenas relaciones con los clientes y el servicio al cliente se han resaltado como factores importantes para el éxito de las pymes (Ghosh & Kwan, 1996;Meegan & Taylor, 1997;Wijewardena & Cooray, 1996). En su estudio de las empresas de alta tecnología, Räsänen (1999) puso de manifiesto la importancia de una estrecha relación con los clientes (también Halborg et al 1997).…”
Section: Características Del Servicio Y La Supervivenciaunclassified